PROGRESSIVE FAILURE ANALYSIS OF FILLED HOLE CFRP PLATE IN COMPRESSION LOADING - Fatokah, Imam
Composite materials are materials commonly used in various aircraft structures. Lately, some components of fighter aircraft have begun to use a lot of composite material. Therefore, research for the development of continuous composite materials needs to be carried out by researchers. In this study, it was focused on the effect of compressive loading on hollow composite plates with fill holes. Observations are made on the pattern that occurs by testing. Specimen testing starts from the manufacturing stages of composite panel manufacturing to form specimens, then compression testing is carried out based on ASTM D6742 standard compressive filled hole testing. Tests were carried out on four configurations with two unidirectional (UD) configurations namely UD-8186 and UD-8188 and two fabric configurations namely Fabric-8284 and Fabric-8286. The results showed that the maximum average load of each configuration for UD- 8186 was 349.95 MPa, UD-8188 was 402.83 MPa, Fabric-8284 was 329.78 MPa, Fabric-8286 was 433.21 MPa.